Sistem fisik - Makna budaya Bali dalam arsitektur Restoran Three Monkeys di Sanur Bali - Sombu, Alwin Suryono; Adityavarman, Ryadi; Talan, John Petrus (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Bali's Sanur tourism sector is home to many well-known structures with unique, non-Balinese architectural styles. This paper aims to expose the Balinese physical-meaning system found in the Three Monkeys restaurant's architecture in Sanur. The approach is descriptive; first, the "physical" architecture is explained, followed by the "purpose of existence" and "essence." Open frontage, bottom level raised over the terrace, and an alang-alang roof supported by bamboo poles. There is an open figure to the left and north, with bamboo trees around it and a glass-block wall atop. a blend of Balinese traditional and modern architecture. The arrangement: an open pool acts as a mediator between the dining room, kitchen, and bathroom; the terrace is shaded by frangipani trees, and there is a place of prayer in the northeast corner. The upper rooms are conditioned, enclosed by glass walls, modern compared to the lower rooms. The terrace materials are traditional (alang-alang roof, parasol stone wall - bamboo), the lower dining room is a mix of traditional (bamboo wall, alang-alang roof, wooden furniture) and modern (polished concrete floor, glass-block wall), and the upper room is modern (frameless glass wall, stainless-steel railing). The traditional-modern Balinese blend is displayed through the building's figure, layout and materials.